Immigrant Diversity and Long-Run Development - Luigi Minale; Rudi Rocha; Bruno Vigna (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
The article investigates the long-term economic effects of immigrant diversity. Focusing on the large immigration wave experienced by Brazil at the turn of the twentieth century, we ask whether municipalities in the State of S\~ao Paulo that received a population of immigrants characterized by a more diverse mix of origin countries ended up having better long-term economic outcomes. To identify causal effects, we leverage on unique historical individual-level data in immigrants arriving in S\~ao Paulo between 1880 and 1920, and develop an instrumental variable strategy that combines time variation in the composition of immigrants arriving from overseas with the timing of the railway network expansion in the state. We find that a one standard deviation increase in accumulated immigrant diversity in 1920 is associated with a 7-8% higher income per capita in 2000. This effect is economically relevant and robust to various identification tests. Furthermore, when exploring the mechanisms through which immigrant diversity affected long-term development, we document that municipalities that hosted more a more diverse pool of immigrants experienced (i) larger proportions of employment in manufacturing and services as well as greater occupational diversity within manufacturing in the long-term; (ii) higher investment in public goods, as measured by municipal spending on education; (iii) and higher education outputs in the long-run.
Keywords: C36; N36; O15; 330; birthplace diversity; immigration; long-term development